Digital Personal Branding Konten Kreator Penyiar Melalui TikTok - Djeke, Stella Clarissa; Paramita, Sinta (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Social media is a place for the personal branding of internet users. In Indonesia, TikTok is the social media that ranks 2nd with the largest number of users. This is because this social media features audiovisual content accompanied by interesting features. Raye Shabrina is a private radio broadcaster in Jakarta who actively creates content on the TikTok platform. Initially, she uploaded content in the form of duets with foreign broadcasters. The content evolved into broadcast and public speaking exercises. By using the netnography method that utilises data through social media, the researcher intends to find out how Rayes Shabrina builds a positive image through her TikTok account @rayeshabrina. The application of the concept of The Eight Laws of Personal Branding by Peter Montoya (2004) is a reference in finding out the relevance between the concept and the content uploaded by Raye Shabrina. Data collection was carried out by pulling data through the Analisa.io website, supported by interviews, observation, and documentation. This research shows that as a broadcaster, the interviewee succeeded in doing digital personal branding by presenting the image of an educative broadcaster in a cheerful and enthusiastic manner and being consistent in creating content. Media sosial merupakan wadah personal branding para pengguna internet. Di Indonesia, TikTok merupakan media sosial yang menempati urutan ke-2 dengan pengguna terbesar. Hal ini karena media sosial ini menampilkan konten audiovisual disertai dengan fitur menarik. Raye Shabrina merupakan penyiar radio swasta di Jakarta yang aktif membuat konten pada platform TikTok. Awalnya, konten yang diunggah berupa duet dirinya dengan penyiar luar negeri. Konten berkembang menjadi latihan siaran dan public speaking. Dengan menggunakan metode netnografi yang memanfaatkan data melalui media sosial, peneliti bermaksud mencari tahu bagaimana Rayes Shabrina membangun citra positif melalui akun TikTok @rayeshabrina. Penerapan konsep The Eight Laws of Personal Branding oleh Peter Montoya (2004) menjadi acuan dalam mencari tahu relevansi antara konsep tersebut dengan konten yang di unggah Raye Shabrina. Pengumpulan data dilakukan dengan menarik data melalui website Analisa.io didukung dengan wawancara, observasi dan dokumentasi. Penelitian ini menunjukkan bahwa sebagai seorang penyiar, narasumber berhasil melakukan digital personal branding dengan menampilkan citra seorang penyiar edukatif dengan pembawaan yang ceria dan semangat serta konsisten dalam membuat konten.